Isoenzyme Variation in Medicago sativa Ecotypes - Sengul, Meryem; Agar, Guleray; Sengul, Suleyman (Asian Journal of Chemistry, 2010)
This study was carried out in order to determine variation of Medicago sativa ecotypes, using poliacrilamide slab gel electrophoresis (PAGE) on the 5 enzyme systems (peroxidase, malate dehydrogenase, polyphenol oxidase, superoxide dismutase, glutamate). Differences between ecotypes were analyzed statistically. The highest genetic distance was between Manyas and Refahiye ecotypes, the least was between Manyas and Acipayam ecotypes. The results from isoenzyme analysis correlated with some morphological characteristics. This study of Medicago sativa ecotypes suggested that the geographical and ecological distribution of the plants contributes to higher genetic similarity.